Análise de lacunas no mercado Praxis - Almeida, Rui Pedro da Silva (2021)
Praxis is a platform that allows students to search internship offers submitted by companies, research labs and higher education institutions. The success of the platform depends on its adoption by students that use keywords to find internships and organizations that need candidates to fill their vacancies. The two problems detected with the platform are the high number of searches without results and the low percentage of internships with candidates. This work explores text mining techniques with the objective of creating a tool to analyse the discrepancy between supply and demand, helping to identify market gaps and possible improvements to the search engine. The final solution allows Praxis administrators to intuitively analyse the available data on a dashboard. Additionally, from the analysis made, limitations were found on the existing search engine, so an improved one was created. Software engineering best practices were followed and the defined objectives were achieved.